Employees Job Satisfaction in Rural and Urban Enterprises of Unequal Capacities: The Russian Review - V. Blinova, Tatiana; A. Vyalshina , Anna (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study was to conduct a comparative analysis of the job satisfaction level of the rural and urban population employed in enterprises of various capacities and to assess the social concerns of the job loss risks. Materials and methods: The empirical base of the study was the data of 26 waves of the Russian Longitudinal Monitoring Survey (RLMS-HSE). The analysis of multivariate distributions of respondents' answers was carried out using the statistical data processing package STATISTICA Advanced for Windows 10.0. Results of the study demonstrated that rural residents engaged in large-scale enterprises and small businesses are most fully satisfied with their jobs. Considering the overall assessment of ‘fully satisfied’ and ‘rather satisfied’ responses, the maximums are peculiar to urban and rural residents employed in large enterprises; the second place is occupied by urban residents working in small businesses and rural residents employed in medium-sized enterprises; the very least job satisfaction was manifested in the city people and villagers employed in micro-enterprises. An integral assessment of job satisfaction was performed along with its structural elements; noteworthy was the low satisfaction of workers of all types of enterprises with their wages. The proportion of respondents who were completely satisfied with wages was at the lowest possible level and ranged from 5.7% to 11.9%. Urban residents were more satisfied with the working conditions than villagers, regardless of the capacity of the enterprise; microenterprises staffers were least satisfied with the prospects for professional growth. The proportion of people with higher education satisfied with their employment was higher than in less educated people. Job satisfaction in rural women was higher than in urban women; it also manifested the tendency to increase with the capacity of the enterprise. Most of the rural youth aged 16-30 were satisfied with the work in small and medium-sized enterprises; the urban youth graded large-scale and small enterprises higher than the rest. Workers over 60 exhibited the highest job satisfaction, which is explained not only by the accumulated professional experience but also by the dishonorable amounts of retirement benefits. The greatest social concerns associated with job loss risks were peculiar to rural workers employed in micro- and largescale enterprises; such concerns manifested a tendency to increase in the cities with the increase in the enterprise capacity. Conclusion: It was concluded that differences in the job satisfaction level in rural and urban populations are explained both by the heterogeneity of jobs and the heterogeneity of the socio-demographic characteristics of the workers themselves.